The Synergistic Antibacterial Mechanism of Gentamicin-Loaded CaCO3 Nanoparticles - Pan, Xiaohong; Chen, Saili; Li, Dongzhe; Rao, Wenhua; Zheng, Yilin; Yang, Zhaoyuan; Li, Lan; Guan, Xiong; Chen, Zhi (Frontiers in Chemistry, 2018)
In the present study, we used CaCO3 nanoparticles (CCNPs) as carriers to assess the physicochemical characteristics and antibacterial effect of gentamicin sulfate (GS)-loaded CCNPs (CGPs). The results indicated that CCNPs had relatively regular chain-like structure, and the size of the crystallites was around 62.5 nm. FT-IR analysis indicated that the GS could effectively load onto CCNPs. Meanwhile, the dosage of CCNPs would affect the drug loading and entrapment efficiency of GS. CCNPs could prolong the release of GS, and the complete release of GS from CCNPs was extended up to 24 h. Additionally, CCNPs could obviously increase the antibacterial effect of GS. The zeta potential analysis and microscopic investigations indicated that the adsorbed CCNPs could increase the damage level of bacterial cell wall and enhance the permeability of cell membranes, leading to increased bacterial death.